(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
In recent years, more and more researchers presented their graphic representations for protein sequence. Here, we present a new 2D graphic representation of protein sequence based on four physicochemical properties of 20 amino acids. By this graphic representation we define a distance calculation formula to quantificationally calculate the similarity degree of different protein sequences. Then we apply the proposed graphical curve and new distance in the similarity/dissimilarity comparison of 10 ND5 proteins and the protein sub-cellular localization prediction about two common test datasets, ZD98 and CL317. The results show the proposed method is easy and effective.